2015
DOI: 10.1186/s12884-015-0556-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise mode on pregnancy outcomes: ENHANCED by Mom project

Abstract: Background: The extent of the benefits of exercise training during pregnancy on maternal, fetal, and neonatal health outcomes has not been sufficiently addressed. While aerobic exercise training has been determined as safe and efficacious throughout pregnancy, the effects of other training modes on fetal health and development as well as any continued benefits for the neonate, especially with regards to cardiovascular development and function, is largely unknown. In the ENHANCED by Mom study we aim to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…Few other studies have examined changes in heart development associated with maternal exercise. There is evidence that exercise during pregnancy may influence the maturation of cardiac autonomic control and increase right ventricular cardiac output in children [192,193], and improve NO bioavailability and vascular function in the fetus of pigs [194].…”
Section: Maternal Exercise Reduces Incidence Of Chds From Pregestamentioning
confidence: 99%
“…Few other studies have examined changes in heart development associated with maternal exercise. There is evidence that exercise during pregnancy may influence the maturation of cardiac autonomic control and increase right ventricular cardiac output in children [192,193], and improve NO bioavailability and vascular function in the fetus of pigs [194].…”
Section: Maternal Exercise Reduces Incidence Of Chds From Pregestamentioning
confidence: 99%
“…This study employed a secondary data analysis using data from a prospective randomized study (ENHANCED by Mom) focused on the in uence of exercise type on infant outcomes throughout pregnancy (18). Women were recruited from local obstetric clinics via brochures, yers, word-of-mouth and social media in eastern North Carolina.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Davenport et al (2016), current evidence suggests that D r a f t blood flow delivery to the fetus is maintained during exercise, although the mechanisms underlying the protection of blood flow to the fetal unit are largely unknown. Current studies have found that the fetal heart adapts to exercise training, resulting in fetal cardiovascular adaptations to maternal exercise, including fetal heart rate modulation and improved autonomic control (May et al 2010, Moyer et al 2015. Studies have identified positive correlations between fetal heart adaptability and heart rate variability in response to maternal aerobic and resistance exercise training during pregnancy, with more fetal cardiovascular adaptations occurring in response to exercise of higher intensity and of longer duration (May et al 2012).…”
Section: Exercise-induced Alterations In Placental Developmentmentioning
confidence: 99%